Marital Adjustment and Marital Relationship among Indian Merchant Seamen - Paul, Nisha (Journal of Social Work Education and Practice, 2023)
Marriage is a society approved way of establishing a family of procreation. Its purposes, functions and forms may differ from society to society, but it is present everywhere as an institution (Jeejan, J, 2003). The quality of marital adjustment is a crucial factor in marital relationships. Work nature of merchant seamen is full of dangerous living conditions and unbearable working conditions Other than that they have to stay away from their family for long period. It results in less quality time with their families. In this study researcher descriptive research design has been adopted for the study and probability sampling method has been used to select the respondents of the study to understand the marital relationship and marital adjustment among the Indian merchant seamen.